Penerimaan Masyarakat terhadap Proyek Pengadaan Tanah Desa Bungkukan Kabupaten Kotabaru: Sebuah Kajian Sosiologi Hukum - Ismar Hamid; Siti Zulaikha; Yusril Yusril; Rachmat Hidayat; Rahmat Nur; Wafiq Mustakimah; Halimah Halimah; Yudiarto Arman (Universitas Lambung Mangkurat, 2026)
The feasibility study for land acquisition in Bungkukan Village, Kotabaru Regency, is a strategic project to support the development of an urban service center, as regulated by the Kotabaru Regency Regional Regulation No. 6 of 2025. This research aims to assess the technical, legal, and social feasibility of the project using a socio-legal approach. The specific objectives include identifying the location, area, and status of the required land , evaluating its legal and social feasibility , and analyzing potential social impacts and land conflicts. Key findings indicate that while the project aligns with national spatial and development plans , there is significant potential for conflict due to unclear land ownership status and public concerns regarding compensation processes. The study concludes that it is necessary to conduct a thorough verification of land rights and formulate mitigation strategies that focus on transparent dialogue, fairness, and community participation. The results of this study are expected to serve as a basis for the Local Government to implement a just and sustainable land acquisition process.